Human pharmacokinetics of XBD173 and etifoxine distinguish their potential for pharmacodynamic effects mediated by translocator protein. Issue 9 (20th May 2022) - Owen, David R.; Phillips, Alexandra; O'Connor, Desmond; Grey, Gabrielle; Aimola, Lina; Nicholas, Richard; Matthews, Paul M.
Abstract : XBD173 and etifoxine are translocator protein (TSPO) ligands that modulate inflammatory responses in preclinical models. Limited human pharmacokinetic data is available for either molecule, and the binding affinity of etifoxine for human TSPO is unknown. To allow for design of human challenge experiments, we derived pharmacokinetic data for orally administered etifoxine (50 mg 3 times daily) and XBD173 (90 mg once daily) and determined the binding affinity of etifoxine for TSPO. For XBD173, maximum plasma concentration and free fraction measurements predicted a maximal free concentration of 1.0 nM, which is similar to XBD173 binding affinity. For etifoxine, maximum plasma concentration and free fraction measurements predicted a maximal free concentration of 0.31 nM, substantially lower than the K i for etifoxine in human brain derived here (7.8 μM, 95% CI 4.5–14.6 μM). We conclude that oral XBD173 dosing at 90 mg once daily will achieve pharmacologically relevant TSPO occupancy. However, the occupancy is too low for TSPO mediated effects after oral dosing of etifoxine at 50 mg 3 times daily.